Prognostic significance of vascular endothelial growth factor expression in adult patients with acute myeloid leukemia: a meta-analysis. Issue 7 (July 2013) - Guo, Baoping; Liu, Yan; Tan, Xiaohong; Cen, Hong
Abstract: The prognostic significance of angiogenic markers remains controversial. Many studies have suggested that vascular endothelial growth factor (VEGF) or vascular endothelial growth factor receptor (VEGFR) overexpression correlates with poorer survival in adult patients with acute myeloid leukemia (AML), but some studies suggest a greater probability of survival. To investigate the prognostic significance of VEGF overexpression in adult AML, we performed a meta-analysis of the published studies that provided survival information according to VEGF expression status. Pooled hazard ratios (HRs) indicated that VEGF overexpression had a poor impact on the survival of adult patients with AML. The combined hazard ratio for event-free survival (EFS) was 1.40 and summary HR for overall survival was 1.54. The pooled HR was 1.92 in AML by enzyme-linked immunosorbent assay and 1.67 in AML by immunohistochemistry. These findings indicate that VEGF overexpression has an adverse impact on prognosis for patients with AML. VEGF may become a useful prognostic factor in the context of targeted therapy for patients with adult AML.